Attitude and practices of parents toward their children's oral health care during COVID-19 pandemic - Mridula Goswami; Monika Grewal; Aditi Garg (Wolters Kluwer Medknow Publications, 2021)
Rationale: The impact of COVID-19 has affected billions of people affecting nearly all domains of life, including patient's healthcare needs. Due to constrained dental services during lockdown, pediatric dental needs were severely compromised therefore, parental attitude and practices of maintaining child's oral hygiene impose significant impact on child's oral hygiene. Aim: This study aims to assess the attitude and practices of parents toward their children's oral health care during COVID-19 pandemic. Methodology: The present cross-sectional study was conducted with a sample of 120 parents selected randomly from the outpatient department after obtaining informed consent. A structured questionnaire was used to assess attitude and practice of parents toward their child's oral hygiene during lockdown in COVID-19 pandemic. Results: The overall attitude and practice score of parents in maintaining their child's oral hygiene was low, with mean value of 2.36 ± 1.36 and 2.51 ± 1.50, respectively. 60.8% of parents reported the need of dental treatment for their child during the lockdown period whereas 50.8% parents contacted the dentist during this period; majority (37.5%) of which reported due to toothache. 68.3% of parents would like to visit nearby dental hospital for emergencies during lockdown period. Only 33.3% of parents took extra efforts to maintain their child's oral hygiene while 45% made dietary changes in their child's diet to prevent tooth decay. Conclusion: The overall attitude and practices of the parents were poor toward the oral health of their children during the lockdown period in COVID-19 pandemic. There is urgent need of increasing awareness among parents regarding the importance of maintaining their child's oral health. The inability to see the doctor should at least encourage better home practice measures for future. The concept of tele-dentistry is very new and will be the need of the coming modern times.